Update on Controls for Isolation and Quantification Methodology of Extracellular Vesicles Derived from Adipose Tissue Mesenchymal Stem Cells - Franquesa, Marcella; Hoogduijn, Martin J.; Ripoll, Elia; Luk, Franka; Salih, Mahdi; Betjes, Michiel G. H.; Torras, Juan; Baan, Carla C.; Grinyó, Josep M.; Merino, Ana Maria (Frontiers in Immunology, 2014)
The research field on extracellular vesicles (EV) has rapidly expanded in recent years due to the therapeutic potential of EV. Adipose tissue human mesenchymal stem cells (ASC) may be a suitable source for therapeutic EV.A major limitation in the field is the lack of standardization of the challenging techniques to isolate and characterize EV. The aim of our study was to incorporate new controls for the detection and quantification of EV derived from ASC and analyze the applicability and limitations of the available techniques. ASC were cultured in medium supplemented with 5% of vesicles-free fetal bovine serum. The EV were isolated from Conditioned Medium by differential centrifugation with size filtration (0.2 µm). As a control, non-conditioned culture medium was used (Control Medium). To detect EV, electron microscopy, conventional flow cytometry and Western Blot were used. The quantification of the EV was by total protein quantification, Exo-ELISA immunoassay, and Nanosight. Cytokines and growth factors in the EV samples were measured by Multiplex Bead Array Kit. The EV were detected by electron microscope. Total protein measurement was not useful to quantify EV as the Control Medium showed similar protein contents as the EV samples. The Exo-ELISA kits had technical troubles and it was not possible to quantify the concentration of exosomes in the samples. The use of Nanosight enabled quantification and size determination of the EV. It is however not possible to distinguish protein aggregates from EV with this method. The technologies for quantification and characterization of the EV need to be improved. In addition, we detected protein contaminants in the EV samples, which make it difficult to determine the real effect of EV in experimental models. It will be crucial in the future to optimize design novel methods for purification and characterization of EV.